3(6k+6)=90

Simple and best practice solution for 3(6k+6)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(6k+6)=90 equation:



3(6k+6)=90
We move all terms to the left:
3(6k+6)-(90)=0
We multiply parentheses
18k+18-90=0
We add all the numbers together, and all the variables
18k-72=0
We move all terms containing k to the left, all other terms to the right
18k=72
k=72/18
k=4

See similar equations:

| (3+y)/2=(y+1)/4 | | 5-6a=-6a+5 | | -143+x=64-8x | | -1x+55=16 | | 125x-100+38,600=41,000-175x=x | | h/7=-6 | | 5x+3(x+40)=28 | | 4z+35=9z | | 9w=-9 | | Yx8=4 | | (x+3)/2+1=4.5 | | 3s=-10+8s | | -144-14x=-8x+60 | | f÷6.9=12.8 | | 5t=14=-14 | | 3z+37=42z-2 | | y/2=y+1/8 | | -26+3x=-52-3x | | -2x^2+24=8x | | 10=6+17-16t^2 | | -3+7(-1+8v)=214 | | 14m-17=39 | | 7+2n=-8+5n | | 8u+19=11u-5 | | 10x-5+105=180 | | 2(4-2x)=-32 | | B=12.4b+6= | | −3x^2−6x+189=0 | | -31-6x=33-2x | | e-1.95=2.97 | | v/2+6=9 | | -5w=-6w-10 |

Equations solver categories